Implementing Major Trauma Audit in Ireland. Issue 1 (January 2016) - Deasy, Conor; Cronin, Marina; Cahill, Fiona; Geary, Una; Houlihan, Patricia; Woodford, Maralyn; Lecky, Fiona; Mealy, Ken; Crowley, Philip; ,
Abstract: Background: There are 27 receiving trauma hospitals in the Republic of Ireland. There has not been an audit system in place to monitor and measure processes and outcomes of care. The National Office of Clinical Audit (NOCA) is now working to implement Major Trauma Audit (MTA) in Ireland using the well-established National Health Service (NHS) UK Trauma Audit and Research Network (TARN). Aims: The aim of this report is to highlight the implementation process of MTA in Ireland to raise awareness of MTA nationally and share lessons that may be of value to other health systems undertaking the development of MTA. Methods: The National Trauma Audit Committee of the Royal College of Surgeons in Ireland, consisting of champions and stakeholders in trauma care, in 2010 advised on the adaptation of TARN for Ireland. In 2012, the Emergency Medicine Program endorsed TARN and in setting up the National Emergency Medicine Audit chose MTA as the first audit project. A major trauma governance group was established representing stakeholders in trauma care, a national project co-ordinator was recruited and a clinical lead nominated. Using Survey Monkey, the chief executives of all trauma receiving hospitals were asked to identify their hospital's trauma governance committee, trauma clinical lead and their local trauma data co-ordinator. Hospital Inpatient Enquiry systems were used to identify to hospitals an estimate of their anticipated trauma audit workload. Results: There are 25 of 27 hospitals now collecting data using the TARN trauma audit platform. These hospitals have provided MTA Clinical Leads, allocated data co-ordinators and incorporated MTA reports formally into their clinical governance, quality and safety committee meetings. There has been broad acceptance of the NOCA escalation policy by hospitals in appreciation of the necessity for unexpected audit findings to stimulate action. Conclusion: Major trauma audit measures trauma patient care processes and outcomes of care to drive quality improvement at hospital and national level. MTA will facilitate the strategic development of trauma care in Ireland by monitoring processes and outcomes and the effects of changes in trauma service provision.